ANALISIS GIZI DAN LATIHAN CIRCUIT TRAINING TERHADAP PENINGKATAN KONDISI FISIK ATLIT FUTSAL KAB.BANGGAI (Studi Kasus Atlit Futsal Kabupaten Banggai) - Salahuddin, Muhammad; Nurhikmah, Nurhikmah (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2019)
This study aims (1) to determine the relationship of food nutrition intake to physical activity in improving the physical condition of futsal athletes in Banggai Regency. (2) To find out the effect of circuit training exercises on improving the physical condition of Banggai Regency futsal athletes.This study uses a survey method and a questionnaire using data collection techniques using 24-hour food recall by recording the food consumed every day. This study also uses the research design of One Group Pretest-posttest Design, which is a research design that has a pretest before being treated and posttest after being given treatment.Based on the results of data analysis, it can be concluded that the relationship between food intake and physical activity shows that r count food intake on activity was 0.577 with a significance level of 0,000 <0. This shows that there is a relationship between food nutritional intake with physical activity which has an interpretation of the correlation value rather low. So there is a positive relationship of food nutrition intake to physical activity to improve the physical condition of futsal athletes in Banggai Regency. And there is a significant effect of circuit training exercises on improving the physical condition of futsal athletes in Banggai Regency. Based on the t test results obtained value of t arithmetic (6.956)> t table (1.729), and p value <of 0.05. These results can be interpreted that the hypothesis is accepted, so the hypothesis states there is an effect of circuit training exercises on improving the physical condition of futsal athletes in Banggai Regency.